(Un)locking the church doors: regime legitimacy and political (de)mobilisation of churches in Ethiopia. Issue 5 (19th October 2020) - Rhodes, Christopher
ABSTRACT: Drawing upon research including personal interviews with Ethiopian church leaders and examination of Ethiopian laws and constitutions through three consecutive governments over the period 1930–2012, this contribution examines the motivations and strategies by which successive authoritarian governments in Ethiopia have mobilised or demobilised Christian churches. The contribution argues that in contexts of low economic development, the political salience of churches comes not only from their ability to (de)legitimise governments, as argued in previous works, but also from churches' valuable resource mobilisation capabilities and international connections. The contribution explores how successive authoritarian governments in Ethiopia have balanced these political and economic considerations in deciding whether to politically mobilise or demobilise the country's influential Orthodox and Protestant churches and details the legal and policy tools used by governments to manipulate churches' political capacities.